Night and Dana - Davidson, Anya (Minneapolis, MN : Graphic Universe, 2023)
"When special-effects obsessives Dana and Lily begin work on an eco-horror movie, they realize they've been growing apart. But as everything starts going up in flames, Dana begins to forge her voice as a climate activist"--.
new ya book 2023 fall.
Ages 14-18
Grades 10-12
Keywords: Motion pictures -- Production and direction -- Fiction; Friendship -- Fiction; Self-realization -- Fiction; Graphic novels